Hubungan Pengelolaan Sampah Rumah Tangga terhadap Status Kesehatan Penyakit Menular : The Relationship between Household Waste Management and Status Infectious Disease Health - Ulfah Nuraini Karim; Erika Lubis; Aliana Dewi (Fakultas Keperawatan Universitas Andalas, 2022)
Indonesia is the fourth most populous country in the world facing environmental sanitation, especially waste management. Unmanaged household waste could impact community health status. Therefore, the development of household waste management is important. This study used a cross-sectional approach to analyze household waste management related to the health status of infectious diseases. The population is citizens of the Citarum river, Karawang, West Java. Data collection using questionnaires and physical examination. Data analyzed by Kendall Tau test. The study showed that 55.40% of institutional aspects and 66.20% of operational aspects were moderate and 83.80% of aspects financing and retribution were minor to waste management conditions. Infectious disease health status majority were healthy (86.50%). There is a relationship between household waste management and infectious diseases health status (p value= 0.000). Infectious disease health status is related to household waste management. This study recommended the importance of household waste management competencies for the community. The role and commitment of local leadership, namely RT/RW, increased participation and skills of residents in managing household waste, as well as a balance of funding and retribution systems with residents' understanding of PHBS are the keys to optimal household waste management to improve the health status of residents to avoid infectious diseases.